Global Trends in Research on Wild-Simulated Ginseng: Quo Vadis? - Shin, S.; Park, M.S.; Lee, Hansol; Lee, S.; Lee, Haeun; Kim, T.H.; Kim, H.J. (MDPI, 2021)
To the best of our knowledge, no study has systematically reviewed and analyzed the research trends of wild-simulated ginseng (WSG) used for food or medicinal purposes in many countries. WSG, a non-timber forest product, has been traditionally produced using agroforestry practices, and it has been consumed in various ways for a long time. WSG has a great demand in the market due to its medicinal effects, particularly in improving forest livelihoods and human health. Due to the significance of WSG, we conducted this research to explore the global research trends on WSG using systematic review methodology and keyword analysis. We used two international academic databases, the Web of Science and SCOPUS, to extract 115 peer-reviewed articles published from 1982 to 2020. The research subjects, target countries, and keywords were analyzed. Our results indicate four categories of WSG research subjects, namely growth conditions, components, effects on humans/animals, and the environment of WSG, and the case studies were mainly from the Republic of Korea, China, and the USA. Through topic modelling, research keywords were classified into five groups, namely medicinal effects, metabolite analysis, genetic diversity, cultivation conditions, and bioactive compounds. We observed that the research focus on WSG changed from the biological properties and cultivation conditions of WSG to the precise identification and characterization of bioactive metabolites of WSG. This change indicates an increased academic interest in the value-added utilization of WSG.